SRB Measures of Anosov Actions - Weich, Tobias; Guedes Bonthonneau, Yannick; Guillarmou, Colin (Journal of Differential Geometry)

A language-responsive approach to understanding the scalar product: design of a content- and language-integrated teaching-learning arrangement - Lomas, Olga (Proceedings of the Sixteenth ERME Topic Conference on Language and Social Interaction in Heterogeneous Mathematics Classrooms)

Alterungsbedingter Anstieg der Energieaufnahme von Haushaltskältegeräten - Paul, Andreas; Elsner, Andreas; Kasper, Tina; Schumacher, Daniel; Vrabec, Jadran; Hölscher, Heike; Bluemel, Marcus; Wollny, Wenke; Becker, Wolfgang; Brzoska-Steinhaus, Nicola

Der Einfluss des antizipierten subjektiven Unwohlseins auf akademische Prokrastination - Bobe, Julia; Klingsieck, Katrin B.

Pretend Reading. Textproduktion und Mustergebrauch bei Fünfjährigen - Strozyk, Kristina (leseforum.ch)
Contemporary concepts for supporting language acquisition used in daycare centres for children focus on promoting syntax and lexis and are frequently dialogue-based. Giving children opportunities to write mono- logical pieces means their pre-existing implicit knowledge of texts is activated. In a method known as ‘pre- tend reading’, preschool children were asked to ‘read’ aloud a picture book known to them. Data were gathered on four occasions in an approach inspired by design-based research models and settings tailored to the language behaviour demonstrated by the children. Findings clearly show the promising potential of present reading as a means to support language development. Our paper highlights here the use of pat- terning in children’s written production and the paper focuses on the use of chunks in pretend reading.

Planung von Physikunterricht mit sinnvoller Einbettung digitaler Medien: Welches Wissen wird dabei genutzt? - Jordans, Melanie; Riese, Josef (Frühe naturwissenschaftliche Bildung. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Hamburg 2023)

Mehrsprachigkeit wertschätzen und einbeziehen - Niederhaus, Constanze; Havkic, Amra (DaZ/DaF Didaktik. Praxishandbuch für die Sekundarstufe I und II)

Theatrale Bodenlosigkeit. Zum Zusammenhang von intitutioneller, ästhetischer und wissenschaftlicher Widersetzlichkeit im postmigrantischen Theater - Böker, Ines (Postmigrantische Literatur. Grundlagen, Analysen, Positionen)

Der Neue Weltengarten. Jahrbuch für Literatur und Interkulturalität

Deferred Tax Asset Revaluations, Costly Information Processing, and Bank Deposits: Evidence from the Tax Cuts and Jobs Act - Mohrmann, Ulf; Riepe, Jan (Management Science)
We examine how information processing costs affect the extent to which depositors’ use the details in banks’ income statements. Depositors have a unique cost-benefit structure because they are nonprofessional users of financial information and have high information processing costs. At the same time, they benefit from acting quickly because failing banks make payments on a first-come, first-serve basis. This makes it likely that they will react to a prominent summary measure like the reported net income without adjusting for any risk-irrelevant information included in the line items. In our empirical analysis, we investigate depositors’ behavior as driven by the mechanical revaluations of deferred tax assets due to the 2017 Tax Cuts and Jobs Act. Using a difference-in-difference design, we find deposit withdrawals because of this risk-irrelevant information. In cross-sectional tests, we show that the withdrawals are stronger if the information acquisition costs are low, and the information integration costs are high. Overall, our results show that information processing costs are important for understanding depositors’ reactions to accounting information and can lead to deposit flows that cannot be explained by new risk-relevant information. This paper was accepted by Brian Bushee, accounting. Funding: We kindly acknowledge funding by the Werner Diez Foundation [Grant 2024.1] to make this work available under a Creative Commons license. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.03176 .

Integrated renewable energy systems as the basis for sustainable development of energy, water and environment systems - Meschede, Henning; Piacentino, Antonio; Guzovic, Zvonimir; Lund, Henrik; Duic, Neven (Energy)

Bedeutungsfacetten der Beziehungen von Differenzierbarkeit und Stetigkeit im Ein- und Mehrdimensionalen: Ein Blick auf die semantische Ebene - Lankeit, Elisa; Biehler, Rolf (Beiträge zum Mathematikunterricht 2024 - 57. Jahrestagung der Gesellschaft für Didaktik der Mathematik.)

Intuitiver Zugang zu datenbasierten Entscheidungsbäumen - Fleischer, Yannik; Biehler, Rolf (Beiträge zum Mathematikunterricht 2024 - 57. Jahrestagung der Gesellschaft für Didaktik der Mathematik.)

Transitionen zwischen Vektorobjekten in Schulbüchern - Mai, Tobias; Biehler, Rolf (Beiträge zum Mathematikunterricht 2024 - 57. Jahrestagung der Gesellschaft für Didaktik der Mathematik.)

Designing a Concept Inventory for Real Analysis - Bauer, Thomas; Biehler, Rolf; Lankeit, Elisa (INDRUM2024 PROCEEDINGS - Fifth conference of the International Network for Didactic Research in University Mathematics)

BelgienNet – une plateforme pour l’accès aux langues et cultures de la Belgique - Karaca, Resul; Huybrechts, Yves (Synergies Pays germanophones)

Algebraische Konzepte vertiefen und ihre Zusammenhänge im Schul- und Hoch-schulcurriculum verstehen lernen : Design-Prinzipien zur Anregung des Vereinheitlichens mathematischen Wissens im Mathematiklehramtsstudium - Wessel, Lena; Dellori, Anna (Mathematica Didactica)

Status quo of clinical use and scientific value of quality of life and neurocognitive assessment practice in neuro-oncological patients - Lucas, Carolin Weiss; Bumes, Elisabeth; Loução, Ricardo; Jonas, Kristina; Rosengarth, Katharina; Kochs, Sophia; Jost, Johanna; Wiewrodt, Dorothee; Lieker, Emma; Giordano, Frank A.; Golla, Heidrun; Renovanz, Mirjam; et al. (Brain and Spine)

Category naming for intraoperative monitoring of contextual association - Becker, Maura Luisa; Tampier, Carla; Keil, Phillip; Loução, Ricardo; Pieczweski, Julia; Timmer, Marco; Hampl, Jürgen; Kabbasch, Christoph; Jonas, Kristina; Goldbrunner, Roland; Lucas, Carolin Weiß (Brain and Spine)

Digital Media at the Out-of-school Learning Place - A Qualitative Interview Study with Prospective Science Teachers - Wenzel, Annkathrin; Blumberg, Eva (Science Education International)
Children and young people grow up with a wide range of media, which they are expected to use in different settings. One possibility is the use of digital media in out-of-school learning places, which is currently being expanded. However, there has been little research into the combination of the two fields to date. This study was designed to address this research gap. The study focuses on the opinions and attitudes of prospective primary school teachers on this combination. This is of great importance as, due to current developments, prospective teachers could often find themselves in the situation of being able or having to combine the two fields. 20 prospective teachers (M =23 years, SD = 2.6) took part in the interview study. All prospective teachers have a positive attitude toward digital media. However, most of them are very critical of their use in out-of-school learning places. However, they can name some possible applications and advantages. On the other hand, there are hurdles such as technical problems or their missing skills.